How Much is a Full Professor Worth? The Challenge of Attracting the Best Talent - Knobel, Marcelo (International Higher Education, 2015)
There are many factors that motivate the pursuit of an academic career, including academic freedom, prestige, stability, curiosity, among others. However, salary is also key to the future career choices of young talent. In the State of São Paulo, in Brazil, the salary of all public servants is currently tied to the salary of the governor, that, for political reasons, is kept at a rather low value. This fact is already having an effect on thousands of faculty members in the higher education system of the State. In this paper, I discuss how this salary limitation can influence the decision of young talent to follow an academic career and, put at risk a rather well developed higher education system. Furthermore, I discuss this issue in a broader context of strong regulation, a lack of competitiveness to support career development, and how this all undermines the commitment and morale of qualified professors.